Physical properties, resistant starch content and antioxidant profile of purple sweet potato powder after 12 months of storage - Chay Shyan Yea; Gita Addelia Nevara; Kharidah Muhammad; Hasanah Mohd Ghazali; Roselina Karim (International Journal of Food Properties, 2019)
Current work evaluated the effects of 12-month storage, at chilled (4ºC) and ambient (25ºC) temperatures, on the physical properties, resistant starch (RS) content and antioxidant profile of purple sweet potato (PSP) powder. This study revealed two findings: (i) The antioxidant content of food powders was not always reflective of its antioxidant capacity and (ii) Chilled storage could not prevent the loss of RS and antioxidant activity upon 12-month storage. It is suggested that measurements of antioxidant content and antioxidant activity should be performed concurrently on the same sample.